DEMOKRATISASI SELAMA PANDEMI COVID-19: STUDI KASUS RASISME DI AMERIKA SERIKAT: DEMOKRATISASI SELAMA PANDEMI COVID-19: STUDI KASUS RASISME DI AMERIKA SERIKAT - Zulfah, Indy Nurul Auliya Putri (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2021)
The United States has experienced the decline of democracy in the past decade. This study aims to describe the importance of democratization during Covid-19 pandemic with a case study of racism in the United States. Through the concepts of democracy and democratization, with a qualitative approach method, the author intends to analyze the urgency of democratization in the United States in overcoming the increase cases of racism during the Covid-19 pandemic. The result showed that the role of democracy in overcoming cases of racism in the United States had a big influence, both during the pandemic and post-pandemic conditions.